A new species of Eurystyles (Orchidaceae: Spiranthinae) from Costa Rica - Bogarín Chaves, Diego Gerardo (2020)
Eurystyles comprises about 23 species ranging from Mexico to northernArgentina. Six species are recognized in Mexico and Central America and three in Costa Rica. A new species, named E. uxoris, is here described and illustrated based on Costa Rican material. The species is similar to Eurystyles auriculata and E. standleyi, however, it differs by the smaller plants up to 3 cm tall, smaller leaves of less than 1.6 cm long, flowers with brown dorsal sepal and brown lip apex, petals callose or thickened at apex, and a pandurate lip. Information about distribution, habitat, ecology, etymology and phenology of the new species is provided. An updated key to the Costa Rican species of Eurystyles is presented.